Psychological Benefits of Recreational Sports for University Students - Galang Pakarti Mahardika; Jori Lahinda (Universitas Negeri Semarang, 2025)
The current study assesses the psychological impact of university students’ participation in non-competitive physical activities of a recreational nature. One hundred twenty participants completed a six-week recreational sports program on campus consisting of roundnet, beginner level yoga, recreational badminton, music exercise, and cooperative game sets. A quantitative pretest–posttest evaluation was designed for this study using a Likert scale questionnaire (1–5), the Student Stress Scale, and the Psychological Well-Being Survey to measure shifts in psychological state prior to the sports program, and following program completion. Test results suggest that participants experience significant, and positive, psychological movement on ten different scales after engaging in recreational sports. Of the study participants, 74% reported improvement in mental health, and 81% reported decreased levels of stress evidenced by a shift in average stress score levels of 32.4 to 21.1 (−34.8%). A positive psychological shift was reported by 69% of students evidenced by a shift in average Psychological Well-Being Survey scores of 3.1 to 4.0. Also, 83% of students viewed campus recreational sports participation to induce positive affect and 77% reported participation to be low in effort and high in enjoyment. According to the response data, 72% favored non-competitive activities while 80% felt the activities had stimulating and recreational benefits. Additionally, 67% of students said to have improved the balance of academics and physical activity, 71% reported higher social contact, and 64% showed less evidence of academic burnout. Based on the research results, it can be participation in recreational sports has been shown to provide multidimensional benefits, not only in improving mental health but also in reducing stress, improving psychological well-being, strengthening social interactions, and helping prevent academic burnout.